Pengaruh Konten Marketing Shopee Affiliate Program terhadap Keputusan Pembelian Mahasiswa - Salsabila Aulia (International Journal Administration, Business & Organization, 2022)
The purpose of this study was to find out how the influence of marketing content on the Shopee Affiliate Program on student purchasing decisions. The method used in this study is a quantitative descriptive method. The population in this study were some of the Bandung State Polytechnic students with a total sample of 120 respondents. The analytical method used is simple regression analysis and validity test, reliability test, and normality test. Based on data processing using simple regression analysis, R square is obtained which shows a coefficient of determination of 30%. This means that the content of the Shopee affiliate program affects purchasing decisions by 30%.